More Than Just a Pretty Face: Determining the Effects of Priming and Composite Faces on Perceived Attractiveness - Chua, Jacob Austin T. (Animo Repository, 2022)
The broad field of psychology has numerous concepts that have developed throughout the decades, often having correlations with one another. However, an interaction between priming and composite faces is yet to be established. Therefore, this study aimed to determine the main and interaction effects of both variables on attraction. A two-part experiment was conducted. In the first part, the faces and name (priming effect) to be used for the second experiment were determined. Subsequently, the second part consisted of four different conditions, each with a cover story to ensure data accuracy. Each condition contained a specific combination of the face and name priming stimulus from the established factorial design. All conditions consisted of the same questions with the only difference being the provided stimulus. Participants were tasked to answer scenario questions through five responses based on the given face and name combination. Responses were classified as disgusted, embarrassed, neutral, pleased, and excited. Debriefing forms were also provided. The study focused on two primary questions concerning impression and attractiveness, both dependent on the provided male face. Results revealed a significant increase in attractiveness in composite faces for both questions as compared to non-composite faces. Effects of priming and interaction showed insignificant results, indicating the absence of a trend in responses. Thus, the researchers concluded that composite faces resulted in positive first impression responses, as well as higher levels of attractiveness.